Growth and muscle cellularity of diploid and triploid Atlantic cod (Gadus morhua Linnaeus, 1758) larvae - Vargas, Cecilia Campos; Peruzzi, Stefano; Hagen, Ørjan (Journal of Applied Ichthyology, 2015)
Author's accepted version (post-print). This is the peer reviewed version of the following article: Vargas, C.C., Peruzzi, S. & Hagen, Ø. (2015). Growth and muscle cellularity of diploid and triploid Atlantic cod (Gadus morhua Linnaeus, 1758) larvae. Journal of Applied Ichthyology, 31(4), 687-694, which has been published in final form at http://dx.doi.org/10.1111/jai.12792. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving (http://olabout.wiley.com/WileyCDA/Section/id-820227.html).